2020
DOI: 10.5296/ijele.v8i1.16685
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Electronic University a Role Model in Implementing Blended Learning; Exploring the Experience of Female Students in the Department of English Language and Translation

Abstract: This study explores students’ perceptions of blended learning in a Saudi higher education institution; namely, the Saudi Electronic University. SEU is the only university in the Kingdom of Saudi Arabia that offers undergraduate degree programs in complete mandatory Blended Learning mode of education in all courses. The study aims to describe the actual utilization of online learning represented by Blackboard as the official Learning Management System in SEU and to dictate students’ satisfaction with the learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 13 publications
4
6
1
Order By: Relevance
“…The evidence suggests instructors' need to improve their coordination with other instructors, their digital skills and their teaching methodologies to fit the online environment. This result contradicts results presented by Alowedi (2020), who claimed EFL students were pleased with their teachers' performance.…”
Section: Research Question 2: What Are the Challenges Of Implementingcontrasting
confidence: 99%
See 3 more Smart Citations
“…The evidence suggests instructors' need to improve their coordination with other instructors, their digital skills and their teaching methodologies to fit the online environment. This result contradicts results presented by Alowedi (2020), who claimed EFL students were pleased with their teachers' performance.…”
Section: Research Question 2: What Are the Challenges Of Implementingcontrasting
confidence: 99%
“…These results reveal that blended learning offers the potential to tailor the process of language learning to meet students' needs and individual situations. These findings are in agreement with those of previous studies (Al Bataineh et al, 2019;Alowedi, 2020;Alsowayegh et al, 2019;Altunay, 2019;Bukhari & Basaffar, 2019;Hamad, 2017;Ja'ashan, 2020), which asserted that blended learning offers a flexible setting for learning English and is appropriate to the students' learning styles.…”
Section: Research Question 1: What Are the Benefits Of Implementing Bsupporting
confidence: 93%
See 2 more Smart Citations
“…Further research tapping into the opinions, attitudes, beliefs, and reflections on learners' experiences with VLEs showed that VLEs have all a positive effect on learning the foreign language of English (Alsulami, 2016;Al-Washahy & Amaar, 2015;Cavanaugh & Song, 2014;Gulbinskienė et al, 2017). Additionally, more research was done proving that VLEs such as Blackboard Learn were perceived to be effective for creating mutual interactions between students and EFL teachers especially in the time of the COVID-19 Pandemic (Alowedi, 2020;Althobaiti, 2020;Dahmash, 2020;Han & Ellis, 2019). The VLE of Blackboard Learn enables students to use supplementary videos and myriads of other assistive tools that makes learning both fun and easy; it also enables teachers to provide instant or delayed feedback, ask comprehension questions, provide (delayed) written feedback and use multiple effective pedagogical strategies in delivering their lectures and other learning projects that can be posted in discussion boards or e-portfolios (Alowedi, 2020;Dahmash, 2020;Vo et al, 2017).…”
Section: Virtual Education In Foreign Language Education: Perceptions and Attitudesmentioning
confidence: 99%